(untitled) (ENTHYMEMA, 2019)
The article concentrates on Freud’s notion of the uncanny as a key to his poetics. The starting point of the investigation in Freud’s poetics is not his well-known interpretation of E.T.A. Hoffmann, but the narrative elements of his own text who give a clue to his notion of psychoanalysis. As not only a theoretical approach to literature, but also as a practice of poetry, The Uncanny represents an important part of Freud’s poetics.